Sustainable tourism and corporate social responsibility: The case of Zoomarine Algarve - Contreiras, J.; Machado, V.; Duarte, A.P. (I International Congress - Interdisciplinarity in Social and Human Sciences, 2016)
The study here presented is part of a larger research project on sustainable tourism and corporate social responsibility (CSR). It is based on the case study of the theme park Zoomarine Algarve and had a threefold purpose. First, the study sought to examine the opinion of three important stakeholders – employees, visitors and members of the local community – about the socially responsible practices of the theme park. Second, it evaluated the perceptions of the public regarding the impact of the company’s activities on regional development (employability, tourism and economy) and environmental awareness. Last, the study sought to understand if stakeholders’ opinions regarding this company’s engagement in CSR practices are related to the impacts attributed to Zoomarine Algarve’s regular functions. The methodology comprised quantitative research based on a survey administered to convenience samples of the target groups (n = 405). The results reveal that stakeholders have an extremely positive view of the theme park engagement in CSR practices and feel that it contributes significantly to regional development, as well as to raising the environmental awareness of visitors and local communities. The findings also show that perceptions of CSR engagement are positively related with perceived impacts. Based on the results, this study’s multi-stakeholder approach could constitute a useful methodology when evaluating and monitoring sustainable CSR practices of tourism companies in the long term.